Exposure to Carbon Ions Triggers Proinflammatory Signals and Changes in Homeostasis and Epidermal Tissue Organization to a Similar Extent as Photons - Simoniello, Palma; Wiedemann, Julia; Zink, Joana; Thoennes, Eva; Stange, Maike; Layer, Paul G.; Kovacs, Maximilian; Podda, Maurizio; Durante, Marco; Fournier, Claudia (Frontiers in Oncology, 2016)
The increasing application of charged particles in radiotherapy requires a deeper understanding of early and late side effects occurring in skin, which is exposed in all radiation treatments. We measured cellular and molecular changes related to the early inflammatory response of human skin irradiated with carbon ions, in particular cell death induction and changes in differentiation and proliferation of epidermal cells during the first days after exposure. Model systems for human skin from healthy donors of different complexity, i.e. keratinocytes, co-culture of skin cells, 3D skin equivalent and skin explants, were used to investigate the alterations induced by carbon ions (spread-out Bragg-peak, dose averaged LET 100 keV/µm) in comparison to X-ray and UV-B exposure. After exposure to ionizing radiation, in none of the model systems apoptosis/necrosis was observed. Carbon ions triggered inflammatory signalling and accelerated differentiation of keratinocytes to a similar extent as X-rays at the same doses. High doses of carbon ions were more effective than X-rays in reducing proliferation and inducing abnormal differentiation. In contrast, changes identified following low dose exposure (≤ 0.5 Gy) were induced more effectively after X-ray exposure, i.e. enhanced proliferation and change in the polarity of basal cells.